Sikap terhadap status lajang sebagai prediktor ketakutan hidup melajang pada mahasiswa dan peran moderasi usia, jenis kelamin dan status pacaran - Harahap, Farida; Soemowidagdo, Ratih Kurniasari Leman (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2024)
Being single hood has become a choice for young people now. Not a few young people have a positive attitude towards singlehood l and extend their singlehood. Being singlehood occurs because it is involuntary or is an voluntary. However, living permanently singlehood is still considered negative because it is less in harmony with developmental tasks and traditional societal norms. Do people who agree toward singlehood mean they are not afraid of being singlehood? The aim of this research is to determine the relationship between attitudes towards singlehood and fear of being singlehood among college students by controlling the variables of gender, age and romantic relationship status. This research uses a quantitative approach, namely correlational research using control variables. The subjects in this research were 401 college students aged 18-25 years. The online sampling method is to use a covenience sampling. Data were analyzed using partial correlation from Jamovi. Research findings show that there is a significant negative relationship between attitudes toward singlehood and fear of being singlehood in college students (r=-0.289, p<…..) by controlling of gender, age and romantic relationship status. This means that students who agree toward singlehood will be correlated with reduced fear of being singlhoode. These results also show that the fear of being singlehood among college students who are having romantic relationship is smaller than that of students who are not romantic relationship. Gender and age do not influence attitudes towards singlehood and fear of being singlehood.